Data Driven Optimization Approach to Fish Resources Supply Chain Planning in Aceh Province. (August 2019) - Nurdin,; Zarlis, M.; Tulus,; Efendi, Syahril
Abstract: Aceh is one of the provinces in Indonesia that is rich in the potential of marine and fisheries resources. Many fish resources become superior commodities, therefore good planning and management needs to be done. Fish resource data that will be used in this research is large-scale data from the district and city in Aceh province, then a data driven optimization approach is needed. Optimization has become one of the high technology in planning and management in the supply chain. Supply chain networks as logistics and production process from network that is connected between organizational units that operate from suppliers to the community. The supply chain of fish resources is very complex because it is caused by number of factors, such as the diversity of products from fish resources and short expiration periods. In this paper proposes that the supply chain network built consists of suppliers, distribution centers and consumers. The location of suppliers, distribution centers and consumers comes from 10 regions in the province of Aceh, for fish resource suppliers taken from Coastal Fishing Ports (CFP) and Fish Landing Base (FLB).